Evaluating the toxicity of capecitabine-cisplatin versus gemcitabine-cisplatin regimens for palliative chemotherapy in advanced biliary tract carcinoma - Hasan, Tariq; Rahid Sarwar, S. M.; Sarkar, Fatema; Jahan, Ishrat; Mostari, M. Shabnam (International Journal of Research in Medical Sciences, 2024)
Background: Advanced biliary tract carcinoma is a malignancy associated with poor prognosis and limited treatment options. This study aimed to compare the treatment effects in terms of toxicities of Capecitabine-Cisplatin and Gemcitabine-Cisplatin regimens as palliative chemotherapy for ABTC in Bangladesh. Methods: This quasi-experimental study was conducted at the Department of Oncology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, involving 78 patients with histopathologically confirmed ABTC (AJCC Stage IV). Participants were divided into two groups: Arm-A received Capecitabine-Cisplatin, and Arm-B received Gemcitabine-Cisplatin. Treatment response, hematological and non-hematological toxicities were assessed and compared between the two groups. Results: No significant differences in baseline demographic and clinical characteristics were observed between the two groups. Arm-A demonstrated a higher rate of partial response in the final assessment (51.28% vs. 41.03%, p=0.029). Acute hematological toxicities were more frequent in Arm-B, with a higher incidence of Grade 2 and 3 anemia, neutropenia, and leukopenia (p<0.05). Non-hematological toxicities were comparable, except for Hand-Foot Syndrome, which was significantly higher in Arm-A (p=0.03). Conclusions: The Capecitabine-Cisplatin regimen exhibited a different toxicity profile compared to the Gemcitabine-Cisplatin regimen for palliative chemotherapy in advanced biliary tract carcinoma. While both regimens were generally well-tolerated, the Capecitabine-Cisplatin regimen demonstrated lower incidences of hematological toxicities. These findings emphasize the importance of considering toxicity profiles when selecting treatment options for patients with advanced biliary tract carcinoma.